Absorption kinetics of mercury (II) chloride into water and aqueous sodium chloride solution - Kho, F.; Pham, Gia (Elsevier, 2018)
Mercury has been reported to be naturally occurring trace contaminant in the oil and gas reservoirs. In this study, the absorption characteristic of mercury (II) chloride (HgCl 2 ) in water and aqueous sodium chloride (NaCl) solution was investigated. The kinetic parameters of the reaction between HgCl 2 and NaCl is reported for the first time. A semi-batch reactor is used in this work to investigate the absorption process. The solid vaporization method is applied to generate HgCl 2 gas at different concentrations for this study. At the same hydrodynamic condition, the absorption flux of HgCl 2 into water increases from 6.02 × 10 -6 to 10.26 × 10 -6 mol/m 2 .h when absorption temperature is increased from 298 to 333 K. Applying the two-film theory, the absorption of HgCl 2 into water is controlled by the gas phase resistance. The mass transfer coefficient k G does not change with the HgCl 2 concentration in the gas phase significantly, but is affected by the absorption temperature. For the case of absorption of HgCl 2 into aqueous NaCl solution, the absorption flux increases with increasing NaCl concentration and absorption temperature. The mechanism of reaction between HgCl 2 and NaCl is proposed and the reaction rate law follows second order; first order with respect to HgCl 2 and Cl - with the reaction rate constant k 2 =1.09×10 9 exp[Formula presented] m 3 /mol·s.